Recording group and area-specific activity of fattening pigs by using Passive Infrared Detectors on farm - Wurm, Esther; von Jasmund, Naemi; Tiemann, Inga; Rötering, Kathrin Schulze; Büscher, Wolfgang (Frontiers in Animal Science, 2023)
Animal activity in pigs can be a direct indicator of animal welfare. Passive infrared detectors (PID) provide one method of measuring animal activity on the pen level as a cost-effective and easy-to-use sensor technique. The study aimed to test PIDs on different commercial farms with fattening pigs. On each farm, a focus pen was selected and group activity, and activity in the feeding and exploration area was measured by using three PIDs. For data evaluation, three continuous 24h time periods were selected for each farm. Additionally, animal behavior was recorded by video cameras for visual scan sampling. To compare the PID outcome with the recorded behaviors, an ethogram was used to categorize active and inactive behaviors. Using scan sampling, the validation of the PID data was based on still frames at 10 min intervals. In addition, barn climate such as temperature, relative humidity, and ammonia concentration were measured. The analysis of seven farms showed a strong correlation between PID data and visual assessment for group activity from 0.67 -0.91 (p < 0.001; n = 432). For the activity in the feeding area, medium to strong correlations between 0.44 -0.65 (p < 0.001; n = 327) could be found. The PID data for the exploration area reached correlations with a smaller effect strength. Based on the activity data measured by PIDs, a typical diurnal rhythm for pigs could be found for all farms. Moreover, the PID data indicated different activity patterns depending on, e.g., feeding times and sex group composition. The results demonstrated that PIDs can also be used in different housing conditions for measuring animal activity. In combination with barn climate data, the PIDs can provide useful information for the farmer and also characterize farm-specific management.